Assembly of Genetic Circuits with the Mammalian ToolKit - Joao Fonseca; Alain Bonny; Jason Town; Hana El-Samad (Bio-Protocol, 2020)
The ability to rapidly assemble and prototype cellular circuits is vital for biological research and its applications in biotechnology and medicine. The Mammalian ToolKit (MTK) is a Golden Gate-based cloning toolkit for fast, reproducible and versatile assembly of large DNA vectors and their implementation in mammalian models. The MTK consists of a curated library of characterized, modular parts that can be assembled into transcriptional units and further weaved into complex circuits. These circuits are easily repurposed and introduced in mammalian cells by different methods.